Analisis Faktor-Faktor yang mempengaruhi Kinerja Dosen dan Implikasinya pada Kesejahteraan Dosen Perguruan Tinggi Maritim - Setijo Harsono (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2017)
This research is expected to provide inputs for decision-makers in setting policies for the improvement offaculty performance, set formulation and Operational measures to improve lectures performance, and is ableto provide the alternative policy of lrctures performence professor who in turn are able to produce qualifiedgraduates. Sampling taken from the research is based on the number of lectures population who one in 3 (three)Maritime high school, which is a lecturer in the School of Maritime (STIP), Maritime Education and TrainingInstitution (BP3IP), and the Maritime Academy Djadajat as much. Furthermore, from a population of lectures isbased on the number of samples taken Solvin technique and obtained the sample of 181 lecturers. Whileusing the Descriptive Research Method Approach, and verifikatif to test the truth of a hypothesis using PathAnalysis (Path Analysis), in order to get the effects of competence, motivation, facilities and budgeting, andtechnology and information to the performance of lecturers, as well as the recent implications for welfare . Theresults showed as a whole, and together the factors that affect the performance of lectures is the condition ofcompetence, motivation, condition of facilities, infrastructure and technology and information simultaneouslyand contribute significantly to the performance of lectures. The great influence of the factors that affect theperformance of sequential lecturers are as follows; factors that have the greatest contribution is the existenceof a motivating factor, then secondly infrastructure conditions, the factor of technology and information and thelast is of the competence of the lectures. The impact of these factors influence the performance of lectures isalso significantly affect to the performance of lectures welfare.